2013
DOI: 10.3389/fpsyg.2013.00403
|View full text |Cite
|
Sign up to set email alerts
|

Scalar implicatures: working memory and a comparison with only

Abstract: A Scalar Implicature (SI) arises when the use of a relatively weak sentence (e.g., some politicians are corrupt) implies the denial of an alternative, stronger sentence (e.g., not all politicians are corrupt). The cognitive effort associated with the processing of SIs involves central memory resources (De Neys and Schaeken, 2007; Dieussaert et al., 2011; Marty et al., 2013). The goal of this study is to locate this previous result within the current psycholinguistic debate, and to understand at which level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 55 publications
5
71
1
Order By: Relevance
“…While such a sentence is unambiguously a semantic mismatch, it differs from the some ‐related mismatch in ways other than scalar implicature; every and some have different denotations and possibly different verification strategies [see Politzer‐Ahles and Gwilliams, for discussion]. It would be preferable to compare the processing of the implicature‐based “not all” interpretation of some to that of a word which also expresses “not all” but does so without scalar implicatures, for instance, the comparison between processing of some and that of only some [Bott et al, ; Hartshorne et al, ; Marty and Chemla, ; Politzer‐Ahles and Gwilliams, ]. Recently, Shetreet et al [] directly compared number‐based semantic mismatch (e.g., three penguins are on the bus , paired with a picture in which five penguins are on the bus) and some‐based scalar implicature mismatch, and found two conditions activated similar brain regions (i.e., middle frontal gyrus and medial frontal gyrus).…”
Section: Introductionmentioning
confidence: 99%
“…While such a sentence is unambiguously a semantic mismatch, it differs from the some ‐related mismatch in ways other than scalar implicature; every and some have different denotations and possibly different verification strategies [see Politzer‐Ahles and Gwilliams, for discussion]. It would be preferable to compare the processing of the implicature‐based “not all” interpretation of some to that of a word which also expresses “not all” but does so without scalar implicatures, for instance, the comparison between processing of some and that of only some [Bott et al, ; Hartshorne et al, ; Marty and Chemla, ; Politzer‐Ahles and Gwilliams, ]. Recently, Shetreet et al [] directly compared number‐based semantic mismatch (e.g., three penguins are on the bus , paired with a picture in which five penguins are on the bus) and some‐based scalar implicature mismatch, and found two conditions activated similar brain regions (i.e., middle frontal gyrus and medial frontal gyrus).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental work has shown that in a dual task setting people tend to prefer readings without scalar implicatures (De Neys & Schaeken 2007;Marty & Chemla 2013). Facing a broken sentence (with an intervention effect) and perhaps trying to interpret it could require additional cognitive load leading to fewer implicatures, not because implicature suppression is a possible repair strategy, but because participants are expending effort to repair the sentence.…”
Section: Discussionmentioning
confidence: 99%
“…However, their careful analysis identified different possible derivation processes and it is not clear what in the derivation process of a scalar implicature creates an extra cost. The research of Marty and Chemla (2013) suggests that the processing of the alternatives is not the most effortful part in the derivation of implicatures, but that the decision step (the choice between the two readings) is the costly process (however, see van Tiel and Schaeken, 2016). The current data can be interpreted as in line with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%